2019
DOI: 10.1111/apha.13261
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene sodium increases calcium binding by human recombinant cardiac calsequestrin and calcium loading by sheep cardiac sarcoplasmic reticulum

Abstract: Aim: Dantrolene interacts with ryanodine receptors in skeletal and cardiac muscle affecting sarcoplasmic reticulum calcium release. Since dantrolene is lipophilic it could also affect intra-sarcoplasmic reticulum calcium handling proteins such as calsequestrin. This study investigated whether dantrolene (1-30 µmol/L) alters the polymerization state and the calcium binding capacity of recombinant cardiac calsequestrin and cardiac sarcoplasmic reticulum calcium handling. Methods: Human recombinant cardiac calseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Indirect acute cardiac injury in COVID‐19 may occur because of acute coronary dysfunction and ischemic‐perfusion (I/R) injury induced by SARS‐CoV‐2‐mediated cytokine storm 110 . It has been reported that high cytosolic Ca 2+ released from SR in the cardiomyocytes during I/R injury plays a critical role in the progression of acute cardiac injury 136,137 . Fauconnier et al 138 revealed that activation of RyRs is associated with left ventricular damage after I/R injury 139 .…”
Section: Role Of Ryanodine Receptors and Dantrolene In Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect acute cardiac injury in COVID‐19 may occur because of acute coronary dysfunction and ischemic‐perfusion (I/R) injury induced by SARS‐CoV‐2‐mediated cytokine storm 110 . It has been reported that high cytosolic Ca 2+ released from SR in the cardiomyocytes during I/R injury plays a critical role in the progression of acute cardiac injury 136,137 . Fauconnier et al 138 revealed that activation of RyRs is associated with left ventricular damage after I/R injury 139 .…”
Section: Role Of Ryanodine Receptors and Dantrolene In Covid‐19mentioning
confidence: 99%
“…110 It has been reported that high cytosolic Ca 2+ released from SR in the cardiomyocytes during I/R injury plays a critical role in the progression of acute cardiac injury. 136,137 Fauconnier et al 138 revealed that activation of RyRs is associated with left ventricular damage after I/R injury. 139 In addition, prolonged activation of RyRs following I/R injury F I G U R E 6 Role of dantrolene against cardiopulmonary disorders in coronavirus disease 2019 (COVID-19): severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) through activation of ryanodine receptors (RyRs) increases Ca 2+ concentrations causing pulmonary vasoconstriction and development of pulmonary hypertension (PH).…”
Section: Dantrolene and Cardio-pulmonary Disorders In Covid-19mentioning
confidence: 99%
“…But major conclusions, namely similitude between insects and vertebrates in automatism and involvement of Cav channels, Na + /Ca 2+ exchanger and SR Ca 2+ release is without merit, especially, when reported changes in HR is derived from either experimental conditions or artifacts (Figures 3 and 4). Note that even in vertebrate heart cardiomyocyte the estimation of SR release of Ca 2+ is not straight forward, as introducing 24 mM caffeine solution into the chamber dramatically alters the Fluo4 fluorescence signals, though cells were not present yet (Loescher et al, 2019).…”
Section: Neither Ca2+ Clock Nor Hcn Is a Dominant Pacemakermentioning
confidence: 99%
“…Ca 2+ is an intracellular messenger involved in these events. Studies have shown that intracellular Ca 2+ signaling regulates a series of physiological and pathological processes, including energy metabolism, 8 cell proliferation, 9 and apoptosis, 10 and signal transduction, 11 which control abnormal sugar 12 and lipid 13 metabolism and lead to the development of metabolic disorders in various organs 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that intracellular Ca 2+ signaling regulates a series of physiological and pathological processes, including energy metabolism, 8 cell proliferation, 9 and apoptosis, 10 and signal transduction, 11 which control abnormal sugar 12 and lipid 13 metabolism and lead to the development of metabolic disorders in various organs. 14,15 The mitochondrial Ca 2+ unidirectional transporter complex (MCU complex), localized in the inner mitochondrial membrane (IMM), 16 has a certain affinity for Ca 2+ (dissociation constant ≤2 nM) 17 and is a selective Ca 2+ channel that allows mitochondrial Ca 2+ uptake. 18 Over the past 20 years, the MCU complex has been unraveled, and new expectations have emerged about it, which is a complex protein complex including MCU channel proteins and several regulatory subunits.…”
mentioning
confidence: 99%